Effectiveness of the use of aquaaerobics in the process of sectional classes in swimming students 18–19 years - Журавльов, Юрій; Маліков, Микола (Slobozhanskyi Herald of Science and Sport, 2019)
Yuriy Zhuravlev & Nikolai Malikov Purpose: evaluate the effectiveness of the use of aqua aerobics in the sectional swimming lessons program for students aged 18–19 years to improve their overall physical condition. Material & Methods: the study involved students aged 18–19 years (n=46). Evaluation of the effectiveness of aqua aerobics in the process of sectional swimming lessons was carried out on the basis of the results of a comparative analysis of the characteristics of the dynamics of the functional state of the cardiovascular system, external respiration system, the level of functional, general and special physical preparedness of students of the control and experimental groups during the school year. Results: it is shown that the introduction of aqua aerobics into the sectional swimming lessons program for students aged 18–19 years has contributed to a significant improvement in the functional status of the cardiorespiratory system of their body, the level of functional and special physical fitness. At the end of the school year, students of the experimental group were characterized by significantly higher, compared with the control group, the rate of improvement of all indicators of physical condition by 5–14%. Conclusions: the obtained results testified to the high efficiency of using aqua aerobics in the sectional swimming lessons program for students aged 18–19 years in a higher education institution setting.